Scaling of apparatus with mixing device for deep cultivation - Zvarych, A.; Tsarova, A.; Chornyi, Valentyn (My University, 2018)
In this work, the object of scaling were fermenters with a mechanical mixing system for deep aerobic cultivation of the Blakeslea trispora fungus on the medium of beta-carotene microbiological solution. Constructed special computational graphs, calculated simplexes of geometric similarity, coefficients of turbulent transfer and, as a result, calculations of volumetric coefficients of mass transfer.
Keywords: scaling; fermenter; масштабування; ферментер; кафедра процесів і апаратів харчових виробництв